Intranasally administered extracellular vesicles from human induced pluripotent stem cell-derived neural stem cells quickly incorporate into neurons and microglia in 5xFAD mice - Attaluri, Sahithi; Jaimes Gonzalez, Jenny; Kirmani, Maha; Vogel, Andrew D.; Upadhya, Raghavendra; Kodali, Maheedhar; Madhu, Leelavathi N.; Rao, Shama; Shuai, Bing; Babu, Roshni S.; Huard, Charles; Shetty, Ashok K. (Frontiers in Aging Neuroscience, 2023)
Introduction Extracellular vesicles (EVs) released by human-induced pluripotent stem cell (hiPSC)-derived neural stem cells (NSCs) have robust antiinflammatory and neurogenic properties due to therapeutic miRNAs and proteins in their cargo. Hence, hiPSC-NSC-EVs are potentially an excellent biologic for treating neurodegenerative disorders, including Alzheimer’s disease (AD). Methods This study investigated whether intranasally (IN) administered hiPSC-NSC-EVs would quickly target various neural cell types in the forebrain, midbrain, and hindbrain regions of 3-month-old 5xFAD mice, a model of β-amyloidosis and familial AD. We administered a single dose of 25 × 109 hiPSC-NSC-EVs labeled with PKH26, and different cohorts of naïve and 5xFAD mice receiving EVs were euthanized at 45 min or 6 h post-administration. Results At 45 min post-administration, EVs were found in virtually all subregions of the forebrain, midbrain, and hindbrain of naïve and 5xFAD mice, with predominant targeting and internalization into neurons, interneurons, and microglia, including plaque-associated microglia in 5xFAD mice. EVs also came in contact with the plasma membranes of astrocytic processes and the soma of oligodendrocytes in white matter regions. Evaluation of CD63/CD81 expression with the neuronal marker confirmed that PKH26 + particles found within neurons were IN administered hiPSC-NSC-EVs. At 6 h post-administration, EVs persisted in all cell types in both groups, with the distribution mostly matching what was observed at 45 min post-administration. Area fraction (AF) analysis revealed that, in both naïve and 5xFAD mice, higher fractions of EVs incorporate into forebrain regions at both time points. However, at 45 min post-IN administration, AFs of EVs within cell layers in forebrain regions and within microglia in midbrain and hindbrain regions were lower in 5xFAD mice than naïve mice, implying that amyloidosis reduces EV penetrance. Discussion Collectively, the results provide novel evidence that IN administration of therapeutic hiPSC-NSC-EVs is an efficient avenue for directing such EVs into neurons and glia in all brain regions in the early stage of amyloidosis. As pathological changes in AD are observed in multiple brain areas, the ability to deliver therapeutic EVs into various neural cells in virtually every brain region in the early stage of amyloidosis is attractive for promoting neuroprotective and antiinflammatory effects.